Awareness, Attitude, Belief, and Motivation of Health Care Professionals towards Obstetrics and Gynecological Physical Therapy: Awareness and Motivation towards Gynecological Physical Therapy - Taak, Rimsha Hira; Sheikh, Subbayal; Baqir, Syeda Rida; Ishfaque, Soofia; Inayat, Sana; Arzoo, Obaida; Bano, Aniha; Nimrah, . (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
Physical therapy focuses on various health issues of women like: women with pregnancy, after delivery, pelvic floor dysfunction, uterine prolapse, polycystic ovary, and pelvic floor dysfunction was known as Gynecological physical therapy. Healthcare professionals should be aware of and motivate patients toward the significance of physical therapy in gynecological issues. Objective: To determine the awareness, attitude, belief and motivation of healthcare professionals of Karachi towards gynecological physical therapy. Methods: This was a cross-sectional survey-based study that was conducted from January to June 2024, the study population was healthcare professionals from seven districts of Karachi and the sample size was 389, the sampling technique was non-probability purposive sampling. The validated questionnaire was used to evaluate the attitude, beliefs, and motivation of healthcare professionals towards gyne PT. The data were analyzed through SPSS version 23.0. Results: There were 389 healthcare professionals recruited from different districts of Karachi. The level of awareness among the research participants was 36.24%, the belief of research participants regarding the gynae physical therapy was good towards the effectiveness of treatment 44.21% believed that pelvic floor exercises were effective in gynecological problems, 39.33% were highly motivated towards the physical therapy treatment. However, 35.21% thought that the training in the gynecological field was limited and the referral system was thought to be limited by 19.28% of research participants. Conclusion: This study concluded the level of awareness and motivation was good enough among healthcare professionals of our study while there was a lack of referral systems and training programs available in this field of physical therapy.